The Development of The Hidayatul Qori’ fi Qiroati ar-Rasmil Utsmani lil Mubtadi’ Textbook Using the Ummi Method - Hari Prasetia; Jasminto Jasminto; Asriana Kibtiyah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to design, implement, and evaluate the feasibility and effectiveness of the textbook Hid?yatul Q?ri’ f? Qir?ati ar-Rasmil Utsm?ni lil Mubtadi’, based on the Ummi Method, in enhancing elementary madrasah students’ understanding of the Qur’anic writing structure and recitation system by authentic sanad and rasm. The research contributes to the discourse of foundational Qur’anic education, particularly in the introduction of the Uthm?nic script (rasm ‘Utsm?n?) and dhabt rules as employed in the Madinah Mushaf. The lack of structured learning media that integrates contextual learning approaches with the authentic characteristics of the Mushaf motivated the development of this textbook. This study adopts a research and development (R&D) methodology using the ADDIE model—Analyze, Design, Develop, Implement, and Evaluate—systematically applied at MIN 1 Jombang. Data were collected through classroom observations, in-depth interviews, expert validation surveys, and product trials involving 15 fifth-grade students who had previously studied ghor?b and tajw?d using the Ummi Method. The validation results showed an average feasibility score of 86.21%, and field testing indicated significant improvement in the accuracy of recitation and recognition of dhabt symbols. The study’s main contribution lies in pioneering authoritative instructional media on rasm and dhabt for early-level education by combining the strength of qir?’ah transmission (sanad) with a pedagogical design that is visual, repetitive, and auditory. This textbook extends the scope of the Ummi Method toward standardized advanced tajw?d learning. The findings demonstrate that integrating classical methodologies with Mushaf Madinah-based instructional design can establish a strong foundation of recitational accuracy from an early age, making it relevant for adoption by other Qur’anic educational institutions nationally.